Serpentes da Fazenda Nhumirim, Pantanal da Nhecolândia, Mato Grosso do Sul, Brasil : composição e comparações com outras taxocenoses sulamericanas - Silva Junior, Miquéias Ferrão da (2011)
About 82 snake species are already been recorded from the floodplain of the Pantanal. The available information about these snakes, however, is few and punctual. The main goals of this study were to determine the composition of snakes in a locality in the southern Pantanal, sub-region Nhecolândia, Mato Grosso do Sul, Brazil, to analyze the distribution and the abundance of snakes in different vegetation types sampled, and to investigate the faunal similarity between snake assemblages already studied in South America, East of Andes. Snakes were collected at Fazenda Nhumirim from February 2005 to March 2006 during eight campaigns: four in the rainy season and four in the dry season, totaling 82 days of fieldwork not consecutive in five phytophysiognomies using pitfall traps with drift fences. To investigate the snake assemblage similarities, we employed information on 36 studies previously reported in the literature, we performed a cluster analysis using the Bray Curtis index as a measure of similarity and Unweighted Pair Group Method (UPGMA). A total of 242 snakes represented by 34 species were recorded at Fazenda Nhumirim, including two new records for the area. Together, the species Taeniophallus occipitalis, Liophis poecilogyrus, Tantilla melanocephala, Xenodon matogrossensis, Psomophis genimaculatus accounted for 57% of all snakes recorded. Higher numbers of snake species were found in semideciduous forest (19), followed by Cerrado (18) and caronal (17), while in the seasonally flooded grasslands and also in pasture built with exotic grass, six species were found in each. However, higher abundance was observed in caronal with 74 snakes, little more than that obtained in Cerrado and semi-deciduous forest. The analysis of similarity between the local assemblage and 36 other previously studied in South America revealed the formation of three main groups, one group formed mainly by Amazon assemblages, another by the Atlantic forest, and finally, a group formed by assemblages of open formations (Caatinga, Cerrado, Chaco, Pampa, and Pantanal). Although the geographic distances influence the similarity between snake assemblages, geological and climatic factors explain, at least in part, the similarity found between the snake fauna of the Pantanal and other formations of the diagonal of open formations in South America.